Kompensasi Kerja dan Motivasi Kerja terhadap Kinerja Pegawai pada di BBPP Lembang - Jijim Muhammad; Sahromi Sahromi; Muhammad Yusuf Alhadihaq (IPM2KPE, 2023)
This research aims to determine the effect of work compensation and work motivation on employee performance at BPPP Lembang, West Java. This type of research is quantitative research using explanatory methods to determine the influence between the variables studied. The population in this study was all 52 employees at BBPP Lembang. The data analysis used in this research is multiple linear regression analysis using SPSS 23 for Windows software. The results of the research are a contribution for related institutions to pay attention to providing compensation so that employees are motivated to do their work so that they can improve performance so that it has an impact on the organization in achieving its goals. Simulation, that partially and simultaneously compensation and motivation have a positive and significant effect in improving employee performance at BBPP Lembang. Keywords: Work Compensation, Employee Performance, Work Motivation